Pemanfaatan Stiker Untuk Media Pembelajaran Gaya Bahasa Eufemisme Di Kelas Xi Man 1 Sragen - Sari, Isnaini Desiana, Dra. Atiqa Sabadila, M.Hum (2016)
This objectives research are, Describing the form of euphemism language style at sticker use as learning media. Implementationing stickers as learning media euphemism language style. This research uses quality approach. Object of this research is sticker expression contain eufemisme language style. The research resources aretaken from sticker expression contain euphemism language style. The technique of collecting data are observation, see and note technique, and document. The technique of analysing data integrates two technique analysis, first are reduction data, display data, conclusion. The second is continue technique which connect and compare main thing appeal. This research explain thers forms of eufemism language style at sticker. The five forms of eufemism language style at sticker are direct sentence, clause, plesetan, acronym, and traditional poetry. The data collection is 40; devided 13 direct sentences, 3 clauses, 12 plesetan, and 3 acronyms. The last traditional poerty is 5. The reserch result can be referenced for learning eufemism language style appropriate with basic competence (K.D) 3.4 proofread and correct short story text, appropriate with structure and norim text hether spoken and written.